- #1

- 1,067

- 92

Suppose there is one force gravitational force ##\vec{f_g}##. We can relate this downward force and downward acceleration with Newton sec law. This law can be written as ##F_{net,y}=ma_y## which becomes $$-F_g=m(-g)$$ or $$F_g=mg$$

$$\vec{F_g}=-F_g \hat j=-mg \hat j=m\vec g$$.

Is it right? Because there shouldn’t be a -sign with F in first eqn.

What is the first eqn telling?

$$\vec{F_g}=-F_g \hat j=-mg \hat j=m\vec g$$.

Is it right? Because there shouldn’t be a -sign with F in first eqn.

What is the first eqn telling?

Last edited: